Developing Resistivity Contouring and Plume Mapping of Landfill Leachate Using Electrical Resistivity Method in Warri Metropolis - Mamuyovwi Odia; Ify L. Nwaogazie; Gregory O. Avwiri; Eunice O. Nwachukwu (New Ideas Concerning Science and Technology Vol. 6, 2021)
Electrical resistivity method was used to study the movement of municipal solid waste landfills leachate of Niger-Cat, Donparkar and Orhuwhorun dump sites in Warri Metropolis, Southern Nigeria. Landfilling remains the cheapest and one of the most widely practiced method for the disposal of Municipal Solid Waste (MSW) in both developed and developing nations. Both Electrical Resistivity Profiling and Vertical Electrical Sounding (VES) were carried out using Schlumberger array configuration. Surfer 10 and ArcGIS 10.3 software packages were used to interpret resistivity profiling data to produce apparent resistivity contour maps of study sites while IPI2Win software package was used to interpret VES data. This computer program automatically generated model curves using initial layer parameters (resistivity and thickness) derived from partial curve matching of the field curves with standard curves, and calculated the true layer parameters of the geo-electric section. The results revealed that at Niger-Cat dump site, leachate had migrated from dump into surrounding soil and contamination had advanced up to a depth of 19.12m which is within the local groundwater system of the area. At Don-Parkar dump site, results showed leachate migration from around the edges of dump site into surrounding soil and contamination had advanced to a depth exceeding 20.7m. At Orhuwhorun dump site, result of resistivity contour map showed leachate migration on the south of the dump; however VES results showed no contamination; thus groundwater in the vicinity is currently safe. There is need for waste managers to adopt engineered sanitary landfill for solid waste disposal and government policy should address this issue to help safeguard the groundwater resources in the area.